2017
DOI: 10.1088/1742-5468/aa668c
|View full text |Cite
|
Sign up to set email alerts
|

Quasi-stationary states in nonlocal stochastic growth models with infinitely many absorbing states

Abstract: We study a two parameter (u, p) extension of the conformally invariant raise and peel model. The model also represents a nonlocal and biased-asymmetric exclusion process with local and nonlocal jumps of excluded volume particles in the lattice. The model exhibits an unusual and interesting critical phase where, in the bulk limit, there are an infinite number of absorbing states. In spite of these absorbing states the system stays, during a time that increases exponentially with the lattice size, in a critical … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 31 publications
0
4
0
Order By: Relevance
“…For u > 1 previous results [2,4] indicate that the RPM is in a critical phase, with selforganized criticality having a dynamical critical exponent z(u) that decreases continuously with the parameter u. On the other hand, as noticed in [6], in the limit 1/u = 0 the RPM is exactly mapped into the TASEP, a model with quite distinct properties, if the boundary conditions are taken to be open (free) or closed (periodic). For open boundary conditions the model is massive and for the periodic ones the model is critical and belongs to the KPZ critical universality with z = 3/2 and α = 1/2.…”
Section: Discussionmentioning
confidence: 88%
See 2 more Smart Citations
“…For u > 1 previous results [2,4] indicate that the RPM is in a critical phase, with selforganized criticality having a dynamical critical exponent z(u) that decreases continuously with the parameter u. On the other hand, as noticed in [6], in the limit 1/u = 0 the RPM is exactly mapped into the TASEP, a model with quite distinct properties, if the boundary conditions are taken to be open (free) or closed (periodic). For open boundary conditions the model is massive and for the periodic ones the model is critical and belongs to the KPZ critical universality with z = 3/2 and α = 1/2.…”
Section: Discussionmentioning
confidence: 88%
“…Previous evaluations [2] of the dynamical critical exponent z for u ≥ 1 indicate a continuous decrease as u increases, tending to z = 0 as u → ∞. On the other hand, more recently [6] it was observed that the RPM at the limiting case 1/u = 0 recovers exactly the totally asymmetric exclusion problem (TASEP). We can see this correspondence easily from the allowed processes in the particle-vacancy representation of the model.…”
Section: )mentioning
confidence: 95%
See 1 more Smart Citation
“…Internal longrange forces can bring in additional spatiotemporal correlations to such open systems, giving rise to states with a very long lifetime, the so-called "quasistationary states" (QSS) [10][11][12]. Quasistationary states involving spin chains [13], lattices with infinity of absorbing states [14], and in hydrodynamics on a torus [15] have proved the general character of these states.…”
Section: Introductionmentioning
confidence: 99%